Kolaborasi Pendidik dan Orang Tua: Kunci Sukses Membangun Karakter Peserta Didik - Syam, Futri; Adia Nova, Mirza; Ridha, Ismu; Matsam, Risnawati; Subhi, Muhibbul (Indonesian Journal of Teaching and Teacher Education, 2024)
This article discusses the importance of collaboration between teachers and parents in shaping student character through the concept of Tripusat Pendidikan. The research was conducted at SDIT Ar Rahman, Nagan Raya District, using a qualitative method with a descriptive approach. Data were analyzed using the thematic method, which includes data transcription, codification, theme grouping, and interpretation. Data were collected through observation, interviews, and documentation to explore the role of communication between schools and parents in supporting students' character development. Research informants included principals, teachers, parents, and students. The results showed that collaboration between schools and parents has a significant impact on students' character building, both in academic and social aspects. Excellent programs such as Parent-Teacher Meetings and daily reports of student activities create synergy between school and family, ensuring students' character development is monitored on an ongoing basis. The characteristics developed at SDIT Ar Rahman include independence, discipline, honesty, and responsibility. This article recommends strengthening digital communication to facilitate interaction between teachers and parents. In addition, national policies that support close collaboration between schools and families are needed to strengthen children's character education to face future global challenges.